2003
DOI: 10.4049/jimmunol.170.11.5712
|View full text |Cite
|
Sign up to set email alerts
|

T Cells of Atopic Asthmatics Preferentially Infiltrate Into Human Bronchial Xenografts in SCID Mice

Abstract: T cells play an important role in the pathogenesis of bronchial asthma. However, it is not completely known how circulating lymphocytes infiltrate into the airways of asthmatic patients. Because SCID mice are unable to reject xenogenic transplants, many xenotransplant models using various human tissues have been developed. Therefore, to examine the interaction between bronchi and T lymphocytes of asthma, it may be possible to use the human bronchial xenograft and PBMC xenograft in SCID mice. We transplanted hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In particular, lymphocytes obtained from peripheral blood in asthmatics demonstrate a predominance of T-helper lymphocyte type 2 (T H 2, IL 4 producing) immune responses relative to T H 1 (IFN-␥ producing) (33,124). Moreover, Tsumori and colleagues (147) showed that T cells from asthmatic subjects, in particular T H 2 cells, preferentially migrate to bronchial tissue (see Fig. 3), and de Blic and colleagues (28) found that bronchoalveolar lavage samples obtained from highly symptomatic children with asthma show substantially increased ratios of the protein products IL-4/IFN-␥.…”
Section: Dangerous Exercisementioning
confidence: 99%
See 1 more Smart Citation
“…In particular, lymphocytes obtained from peripheral blood in asthmatics demonstrate a predominance of T-helper lymphocyte type 2 (T H 2, IL 4 producing) immune responses relative to T H 1 (IFN-␥ producing) (33,124). Moreover, Tsumori and colleagues (147) showed that T cells from asthmatic subjects, in particular T H 2 cells, preferentially migrate to bronchial tissue (see Fig. 3), and de Blic and colleagues (28) found that bronchoalveolar lavage samples obtained from highly symptomatic children with asthma show substantially increased ratios of the protein products IL-4/IFN-␥.…”
Section: Dangerous Exercisementioning
confidence: 99%
“…We propose that exercise might contribute to this imbalance, leading to exercise-induced bronchoconstriction (EIB). [Data redrawn from Tsumori et al (147).] Table 1.…”
Section: Lessons Learned From Dysregulated Immune Responses To Exercisementioning
confidence: 99%
“…Because it has been shown that several cytokines, such as IL-4, IL-5, IL-2, IFN-γ, were detectable in SCID mice transplanted with human PBLs [41], we only included IL-2 as the representative cytokine in the current study. We found that the isolated PBLs from the serum of model mice did produce certain cytokines, i.e., IL-2 ( Fig.…”
Section: Cellular Physiology and Biochemistrymentioning
confidence: 99%
“…In immune responses, homing of lymphocytes from blood into organs is mediated by a sequential interaction between the lymphocytes and the vascular endothelium in specialized post‐capillary venules (5). In inflamed skin, T cells express the cutaneous lymphocyte associated antigen (CLA) and P‐selectin ligand and the vascular epithelium expresses E‐selectin and P‐selectin (6); however, the adhesion molecules and chemokines for T‐cell homing into airways, lungs and bronchi are not well‐clarified (7).…”
mentioning
confidence: 99%
“…. In inflamed skin, T cells express the cutaneous lymphocyte associated antigen (CLA) and Pselectin ligand and the vascular epithelium expresses E-selectin and P-selectin (6); however, the adhesion molecules and chemokines for T-cell homing into airways, lungs and bronchi are not well-clarified (7).…”
mentioning
confidence: 99%